Temporal Dynamics Between State Attachment Security, Avoidance, and Anxiety: Insights into Everyday Attachment System Functioning - Tammilehto, Jaakko; Kaurin, Aleksandra; Kuppens, Peter; Bosmans, Guy; Vänskä, Mervi; Flykt, Marjo; Peltonen, Kirsi; Lindblom, Jallu (SAGE PUBLICATIONS INC, 2025)
The attachment system regulates behavior to maintain security and cope with insecurities. Although this necessitates the coordination of different attachment states, research on state-level dynamics is scarce. We used data from two ecological momentary assessment studies (Ns = 122 and 127) to examine cross-lagged effects between state attachment security, avoidance, and anxiety. We hypothesized dampening effects between the secure and insecure states. Furthermore, we expected trait-level attachment to moderate the state-level dynamics. Attachment states were assessed seven or ten times daily over a week. Trait attachment was assessed using the Experiences in Close Relationships-Revised. Results showed that state security predicted decreased state avoidance and anxiety. Evidence also emerged for state avoidance predicting decreased security. Trait attachment showed no expected moderation effects on the state-level dynamics. Our study underscores the predominance of security over insecurities, suggesting that the functioning of the everyday attachment system centers on fluctuations in the sense of security.